(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
ABSTRACT- In article quality of plastic details of the oil field equipment depending on modes of production of their various constructions and composition of press materials was reviewed. By adjusting the operating parameters during production of details are defined quality indicators: tensile strength, hardness of details and others. Mathematical dependencies between quality indicators (shrinkage and strength) of details and processing temperature are established. The determination of optimal production rejimes for plastic products requires experimental and theoretical researches, the volume of which increases significantly with the number of shapes and sizes. The organization and conduct of such researches with a view to developing recommendations for the production and operation of these products can lead to a significant expenditure of material and labour resources. In practice of designing of machine details and the equipment for assessment the hazard of a tense situation usually use not criteria of strength, only the safety margin coefficient or equivalent stress. Methods of calculation of equivalent stress are considered on the basis of a method of calculation of equivalent stress is developed that is necessary for practice.